Energy resources investment for industrial virtual power plants under techno-economic uncertainties - Saeed Ghamarypour; Morteza Rahimiyan (International Journal of Electrical Power & Energy Systems)
The energy resources investment in industrial parks is technically and economically important to supply power load of factories with different technical requirements and profitably participate in electricity markets. To achieve these goals, this paper proposes the integration of diverse energy assets as an industrial virtual power plant (IVPP) which provides a great flexibility to the industrial park. The problem of energy resources investment in the IVPP is modeled taking into account the operating features of the industrial parks. The investor seeks to minimize the investment cost of conventional and renewable generating units, as well as storage units, while maximizing the anticipated profit obtained from selling energy to industrial demands and electricity market. A risk-constrained stochastic approach is used to handle the long-term uncertainty in power load, market price, fuel price, and industrial energy tariff while the short- and medium-term variations of power load, renewable energy, and market price are also taken into account. The results through Darab industrial park in Iran show: (i) current economic conditions need serious revisions, e.g., interest rate reduction and subsidy removal on energy carriers, to motivate the energy resources investment, and (ii) under the modified economic conditions and the available budget of K$500, a risk-neutral investor decides the investment of conventional and photovoltaic generating units while a more risk-averse agent prefers to choose only the conventional technology, and decide 88.6% decrement in total generation capacity investment. For a higher budget of K$1500, the investment reduction by taking a more-risk averse strategy reaches 90.1%.